Dwudziestowieczne i współczesne polskie piśmiennictwo na temat dziecka do lat trzech – dziecko „na tle” żłobka, żłobek „na tle” dziecka (wprowadzenie do problemu) - Sadowska, Katarzyna (Biuletyn Historii Wychowania, 2017)
This paper is a review of Polish academic studies into the topic of early child education and care (up to three years of age), published over the course of the 20th Century to the present day, with the main focus on institutional daycare. The majority of academic papers on the subject of early childhood in the context of public institutional daycare were focused on nursing and development, while nursery schools as such were most frequently regarded solely as an alternative to being brought up in a family. The dominant notions in the relevant literature are those of care (including mainly nursing, nutrition and preventative care), development and education. Among the works published after 1945, the majority were nursing handbooks or elaborations on psychology. Certain components of basic early childhood ‘didactics’ can be identified in the papers by Halina Spionek and Hanna Trawińska, as well as in the journals from the 1960s through to the 1980s. The 1970s also saw a number of papers dedicated to the implementation of proper everyday practices into nursery schools and improving the quality of their services. Research on the social spaces of nursery schools was also undertaken in the late 1990s by a team of pedagogues in Łódź, while the economic and social conditions of nursery school operation was examined a group of scholars from the Białystok School of Economics. Currently, the topic of early education in the context of institutional daycare is being explored with growing interest, however, in the overall field of pedagogics it still remains under-researched.